The status of Albanian in relation to the other Balkan languages - Rugova, Bardh (Slavia Meridionalis, 2015)
Albanian has been in contact with other languages almost in all areas in which it is spoken, whereas the relationship with each of them differs from place to place. This study aims at describing the status of Albanian depending on its place of use and on the contacts it has with other Balkan languages.